An Assessment of Contemporary British New Monasticism Framed by the Missional Spirituality of the Celtic Peregrini - Peter Ruxton (Ecclesial Futures, 2024)
From the sixth century, Celtic peregrini (wandering scholars) emerged from Britain and Ireland to establish monastic centres for mission and evangelism. British New Monastic expression would no doubt benefit from increased adoption of their distinctive monastic practices. These practices include the Celtic understanding of the sacramental universe—all creation steeped in the presence of God—all pointing towards the ultimate glory of His kingdom. In risky living they undertook both physical and inner spiritual journeys. They emerged from monastic schools and long periods of seasonal formation. They embraced rhythms of ebb and flow, searching for silence and solitude, to first breathe-in the Holy Spirit, before enthusiastically embarking on evangelism. They drew boundaries—encircling the sacred core, whilst keeping-out distractions. They developed frameworks of daily prayer and Scripture-reading, based on the Psalmody, intentionally building scaffolding—Rules of Life and vows, constantly refocussing themselves on their ultimate goal of prayer without ceasing.